Production and physiological quality of corn lineage seeds as a function of nitrogen doses and moisture at harvest time (Research, Society and Development, 2021)
An initial study on maize lines is essential to obtain hybrids. In the selection of strains, several parameters are observed to reach the crossing and commercialization. Some authors state that adequate nitrogen fertilization is needed to increase the corn economic productivity, considering N is the most required macronutrient by the crop. This nutrient performs diverse metabolic functions in seeds, contributing to their formation and nutritional reserve. Therefore, this paper aimed to evaluate the production and quality of irrigated corn lineage seeds under nitrogen doses and moisture levels at harvest time. The experiment was carried in the experimental area of the Goiano Federal Institute, Ceres Campus, Goiás State (GO), Brazil, and in its SAL. The experimental design was in randomized block, split plots, twenty treatments with five nitrogen rates (50, 110, 170, 230, and 290 Kg ha-1), and harvest took place with four moisture degrees (15%, 25%, 35%, and 45%). A maize line the PGAG10051L. Field and laboratory tests were carried out. The studied strain tolerates low nitrogen availability and has high efficiency in its use. The strain responds positively to the nitrogen increase in relation to germination percentage with better results above 170 Kg of N ha-1. The strain has high capacity to accumulate biomass in caryopsis even with low moisture content. Seeds harvested with 25% moisture showed satisfactory results for germination and vigor. It is recommended to apply 170 Kg de N ha-1 nitrogen dose split in four times for topdressing the corn lineage studied in this paper.